2016
DOI: 10.1149/2.1061608jes
|View full text |Cite
|
Sign up to set email alerts
|

Amorphous TiS3/S/C Composite Positive Electrodes with High Capacity for Rechargeable Lithium Batteries

Abstract: Composite electrodes of a-TiS 3 /S/carbon (Ketjen black; KB) with high capacity were prepared by mechanical milling from a-TiS 3 and S/KB composites. The composites were fabricated into coin type liquid cells and all-solid-state cells and operated as rechargeable batteries at room temperature. The reversible capacity of the coin type liquid cells decreased from 484 to 33 mAh g −1 over 50 chargedischarge cycles, because the polysulfides formed from the redox reactions of a-TiS 3 /S dissolved in the liquid elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Matsuyama et al prepared amorphous TiS 3 /S/C composite electrodes and found poor performance in Li-S batteries with liquid electrolytes when adding TiS 3 to the electrode. 240 It was attributed to LiPS dissolution which is in contrast to other reports 214,[235][236][237][238][239] as it evidences that the capability of TiS 3 to capture LiPSs seems to be very low. However, a remarkable improvement could be achieved with solid electrolytes.…”
Section: Titanium Suldementioning
confidence: 73%
“…Matsuyama et al prepared amorphous TiS 3 /S/C composite electrodes and found poor performance in Li-S batteries with liquid electrolytes when adding TiS 3 to the electrode. 240 It was attributed to LiPS dissolution which is in contrast to other reports 214,[235][236][237][238][239] as it evidences that the capability of TiS 3 to capture LiPSs seems to be very low. However, a remarkable improvement could be achieved with solid electrolytes.…”
Section: Titanium Suldementioning
confidence: 73%
“…We then tried to further improve the electrochemical performance of FeF 2 ‐LYC, by amorphizating it through high‐energy ball‐milling, as amorphous transition metal sulfide cathodes have been reported to exhibit enhanced kinetics and cycling stability compared with the crystalline ones. [ 60–63 ] No apparent diffraction peaks, except for the sealing cover used to protect the sample during characterization, can be observed in the FeF 2 ‐LYC cathode after high‐energy ball‐milling ( Figure A), confirming the amorphous structure of the cathode. A uniform and nanoscale distribution of FeF 2 , LYC, and carbon was achieved in the amorphous cathode based on the elemental mapping results (Figure S12, Supporting Information).…”
Section: Resultsmentioning
confidence: 91%
“…The exact mechanisms for the enhanced kinetics of the amorphous cathode need further study but it may be related to the more uniform, nanoscale distribution of FeF 2 , LYC, and VGCF (Figure S12, Supporting Information) and the increase in the ionic conductivity of amorphous LYC. [60][61][62][63] In addition to the excellent kinetic performance, the amorphous FeF 2 -LYC cathode also exhibit great cycling performance, and the specific capacity is ≈600 mA h g −1 after 100 cycles when testing at 0.1 C at 60 °C after 100 cycles (Figure 5F). The coulombic efficiency of the FeF 2 -LYC cathode kept at a value of higher than 99.7% during cycling (Figure S16, Supporting Information).…”
Section: Electrochemical Characterization Of Crystalline and Amorphou...mentioning
confidence: 99%
“…[ 25–28 ] In previous works, pure amorphous transition metal sulfide cathodes were used as the electrode ASSLBs. [ 29–31 ] However, their electronic conductivity (≈10 −3 S cm −1 ) is four orders of magnitude lower than carbon (≈10 S cm −1 ), [ 32 ] and their ionic conductivity is not particularly stable during the charge–discharge process. In our work, we selected crystal transition metal sulfides, namely, layer‐structured TiS 2 and chevrel‐phase Mo 6 S 8 , which not only have a very stable host structure but also high electronic conductivity.…”
Section: The Concept Of Aea Electrodesmentioning
confidence: 99%